A centrifuge study of the influence of site response, relative stiffness, and kinematic constraints on the seismic performance of buried reservoir structures. Issue 88 (September 2016) - Hushmand, A.; Dashti, S.; Davis, C.; McCartney, J.S.; Hushmand, B.
Abstract: The seismic performance of underground reservoir structures depends on the properties of the structure, soil, and ground motion as well as the kinematic constraints imposed on the structure. A series of four centrifuge experiments were performed to evaluate the influence of site response, structural stiffness, base fixity, and excitation frequency on the performance of relatively stiff reservoir structures buried in dry, medium-dense sand. The magnitude of seismic thrust increased and the distribution of seismic earth pressures changed from approximately triangular to parabolic with increasing structural stiffness. Heavier and stiffer structures also experienced increased rocking and reduced flexural deflection. Fixing the base of the structure amplified the magnitude of acceleration, seismic earth pressure, and bending strain compared to tests where the structure was free to translate laterally, settle, or rotate atop a soil layer. The frequency content of transient tilt, acceleration, dynamic thrust, and bending strain measured on the structure was strongly influenced by that of the base motion and site response, but was unaffected by the fundamental frequency of the buried structure (fstructure ). None of the available simplified procedures could capture the distribution and magnitude of seismic earth pressures experienced by this class of underground structures. The insight from this experimental study is aimed to help validate analytical and numerical methods used in the seismic design of reservoir structures. Highlights: Centrifuge experiments were conducted on underground reservoir structures in sand. Effects of site response, structure stiffness, fixity, and frequency were evaluated. Stiffer structures experienced greater seismic earth pressures and rocking. Fixing the base of the structure amplified accelerations, pressures, and strains. Site response affected accelerations, earth pressures, and strains on structures.